Nanostructural phase transformations in eutectoid reactions of binary alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It is shown that eutectoid reactions of binary alloys are nanostructural processes. The main phase, which decays during the eutectoid reaction, is formed during the crystallization of a metal melt of eutectoid composition. This process is nanostructured. In it, the main elements of microcrystals are the nanocrystals of the alloy components. During the eutectoid reaction, the microcrystals of the main phase disintegrate into nanocrystals. Microcrystals of the other two phases are formed from them.